Using the pedicle screw-U rod system for the treatment of double-level lumbar spondylolysis and isthmic spondylolisthesis - Jiang, Jinghao; Lin, Tao; Chen, Xia; Gao, Rui; Zhou, Xuhui (Frontiers in Surgery, 2024)
Objective: To evaluate the efficacy of pedicle screw-U rod system in treating doublelevel lumbar spondylolysis with or without spondylolisthesis.Methods: A retrospective study was performed. Twenty-six patients were included in this study and followed up at 3, 6, and 12 months. Patients without spondylolisthesis were treated with double U-shaped rods (group I), and patients with spondylolisthesis were treated with a lengthened U-shaped rod (group II). JOA scores, ODI scores, disc range of motion (ROM), intervertebral space height of fixed levels and adjacent levels, and grading of degeneration of adjacent segmental intervertebral disc were evaluated preoperatively and postoperatively.Results: JOA and ODI scores improved significantly at 3 months both in group I and II. The average bone grafting healing time was (6.1±3.1) months for group I, and (6±2.8) months for group II. The intervertebral space heights of L4/L5 and L5/S1were improved significantly at the final follow-up (p<0.05 for both groups). Surgical segmental and adjacent segmental ROM had no significant change at the final followup, in comparison with data preoperatively (p>0.05). No significant changes of intervertebral space height (L3/L4) and grading of intervertebral disc degeneration were noted before and after surgery (p=0.141 and 0.484 respectively).Conclusions: Pedicle screw-U rod system provided advantages of being easy in repairing symptomatic double level lumbar spondylolysis. This technique improved disabilities of patients, preserved the lumbar spine ROM and delayed degeneration of adjacent segments.